FOSTERING THE SPIRIT OF ENTREPRENEURSHIP THROUGH TRANSFORMATIVE LEARNING BASED ON LOCAL WISDOM AT TK IT NURUL HIDAYAH SAMPANG - Ria Astuti; Thorik Aziz; Nisa'el Amala (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2024)
Abstract The purpose of this study was to examine the pattern of transformative learning and the application of transformative learning in developing an entrepreneurial spirit based on local wisdom in IT Nurul Hidayah Kindergarten Sampang. This type of research is descriptive qualitative. Data collection techniques were carried out through participant observation, semi-structured interviews with teachers and principals as well as documentation from the researchers themselves and the IT Nurul Hidayah Kindergarten Sampang. The results of the study indicate that the implementation of transformative learning in fostering an entrepreneurial spirit in early childhood based on local wisdom is carried out with center-based learning or BCCT (Beyond Centers and Circle Time) where children play an active role in learning, while the teacher is only a learning facilitator. Several transformative learning activities in developing the entrepreneurial spirit of early childhood, such as Cooking Class, Market Day, Alms, Healthy Canteen, and Outing Class. Some of the characteristics that want to be instilled in transformative learning in developing an entrepreneurial spirit based on local wisdom in early childhood, namely: independence, courage, confidence, honesty, responsibility, cooperation, mutual help, and creativity. Keywords:  Entrepreneurship, Transformative Learning, Local Wisdom   Abstrak Tujuan penelitian ini adalah mengkaji pola pembelajaran transformatif dan penerapan pembelajaran transformatif dalam mengembangkan jiwa entrepreneurship berbasis kearifan lokal di TK IT Nurul Hidayah Sampang. Jenis penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui observasi partisipan, wawancara semi terstruktur dengan guru dan Kepala Sekolah serta dokumentasi dari Peneliti sendiri maupun dari TK IT Nurul Hidayah Sampang. Hasil penelitian menunjukkan bahwa implementasi pembelajaran transformatif dalam menumbuhkan jiwa entrepreneurship pada anak usia dini berbasis kearifan lokal diselenggarakan dengan pembelajaran berbasis sentra atau BCCT (Beyond Centers and Circle Time) dimana anak berperan aktif dalam pembelajaran, sedangkan guru hanya sebagai fasilitator pembelajaran. Beberapa kegiatan pembelajaran transformatif dalam mengembangkan jiwa entrepreneurship anak usia dini, seperti: Cooking Class, Market Day, Sedekah, Kantin Sehat, dan Outing Class. Beberapa karakter yang ingin ditanamkan dalam pembelajaran transformatif dalam mengembangkan jiwa entrepreneurship berbasis kearifan lokal pada anak usia dini, yakni: kemandirian, berani, percaya diri, jujur, tanggung jawab, kerja sama, saling tolong menolong dan kreatif. Kata Kunci:  Kewirausahaan, Pembelajaran Transformatif, Kearifan Lokal